The Effect of Bitter Melon Extract (Momordica charantia)in Inhibition of NFkB Activation in Leptin treated HUVECS - Purwandhono, Azham; Bumi, Candra (UNEJ e-Proceeding, 2014)
The obesityincreases the riskof morbidityandmortalityof type2diabetesandcardiovasculardisease. Leptin, an adipocytokine that regulate metabolic process, was increase in obesity. Hyperleptinemia activate the transcriptionfactorNuclearFactorKappaB(NF-kB), leading to the occurrence of inflammation. The chronic inflammation in vessels would cause the dysfunction of endothelial cell.Bitter melon (Momordica charantia) has beenused by many peoplefor the treatmentof diseases. Studies showthatbitter melon fruitcontainssaponins(charantins) andalkaloids. This study aimed toinvestigate the effect of bitter melon extract on the level of activated NF-ÎºB. Cultured endothelial cell, HUVECs (Human Umbilical Vein Endothelial), is used for a model of endothelial cells. There are 5 groups: 1) HUVECs culture without leptin as negative control; 2) HUVECs culture with leptin as positive control; and 3 groups given various dosages of bitter melon (0.1 mg/ml; 0.05 mg/ml; 0.01 mg/ml; 0.005 mg/ml; 0.001 mg/ml) and Leptin. Leptin (500 ng/ml) is added on HUVECs to stimulate responds of endothelial cells mimicking obesity condition. Momordica charantiawere given 2 h before leptin treatment. The level of activated NF-KB was measured by ELISA. This study showed that leptin significantly induce NFkB activation and the treatment of bitter melon inhibit NFkB activation significantly (p<0.05). Keywords: Leptin, Endothel, bitter melon, NFkB